2018
DOI: 10.1186/s12877-018-0704-8
|View full text |Cite
|
Sign up to set email alerts
|

Costs of potentially inappropriate medication use in residential aged care facilities

Abstract: BackgroundThe potential harms of some medications may outweigh their potential benefits (inappropriate medication use). Despite recommendations to avoid the use of potentially inappropriate medications (PIMs) in older adults, the prevalence of PIM use is high in different settings including residential aged care. However, it remains unclear what the costs of these medications are in this setting. The main objective of this study was to determine the costs of PIMs in older adults living in residential care. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
71
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 35 publications
6
71
0
1
Order By: Relevance
“…This study describes the staffing mix in residential aged care as operationalised in a clustered domestic model, compared to a standard Australian model. We have previously demonstrated within the same study that this clustered domestic model of care was associated with better consumer‐rated quality of care, quality of life, fewer hospitalisations and potentially inappropriate medications . The clustered domestic model had more PCA hours‐per‐resident‐per‐day, higher levels of training for staff, slightly higher direct care hours‐per‐resident‐per‐day and fewer nurse hours‐per‐resident‐per‐day.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…This study describes the staffing mix in residential aged care as operationalised in a clustered domestic model, compared to a standard Australian model. We have previously demonstrated within the same study that this clustered domestic model of care was associated with better consumer‐rated quality of care, quality of life, fewer hospitalisations and potentially inappropriate medications . The clustered domestic model had more PCA hours‐per‐resident‐per‐day, higher levels of training for staff, slightly higher direct care hours‐per‐resident‐per‐day and fewer nurse hours‐per‐resident‐per‐day.…”
Section: Discussionmentioning
confidence: 76%
“…We recently published findings from a large cross‐sectional study of people living in residential aged care in Australia showing that living in a clustered domestic model (Box ) was associated with a higher consumer‐rated quality of care, quality of life, fewer hospitalisations and potentially inappropriate medications, with similar costs of care and higher direct care hours . However, differences in the staffing structures of the different models of care were not explored in detail.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative RMMR funding model that incorporates clinical audit procedures and ensures the RMMR service is specifically targeted to residents at high risk of medication‐related harm (eg, due to dementia diagnosis or frailty) has been suggested to guide RMMR referral . This may also improve the cost‐effectiveness of running a national medication review program, as the prevalence and cost of PIM use are high …”
Section: Discussionmentioning
confidence: 99%
“…Over three‐quarters of residents in 17 Australian RACFs participating in the INvestigating Services Provided In the Residential care Environment for people with Dementia (INSPIRED) study used anticholinergics, sedatives or PIMs in the previous 100 days . Use of PIMs has been associated with poor health‐related quality of life, poor psychological well‐being, higher medication costs, hospitalisations and increased risk of mortality . Controlled trials of medication review in RACFs in Switzerland, the United States of America (USA) and Northern Ireland have demonstrated that rates of PIM use reduced for residents who received a medication review .…”
Section: Introductionmentioning
confidence: 99%
“…15 The finding of our study is also supported by an Australian study involving 547 participants in residential aged care facilities that showed that people exposed to PIMs (defined by 2015 Beers criteria) were more likely to be older and have a diagnosis of dementia (P = .002). 25 In contrast, a systematic review looking at PIP in people with dementia found that dementia was associated with a decrease in the likelihood of PIMs. 26 In a study from the United States involving participants diagnosed with incident dementia and those without dementia, the prevalence of PIMs use in the 1-year period post diagnosis, as defined by the 2015 Beers criteria, was 69% in people with dementia versus 74% in those without dementia.…”
Section: Prevalence Of Individual Stopp Criteriamentioning
confidence: 97%